Efeito da mitomicina c no epitélio ciliar estudo experimental em coelhos com microscopia eletrônica de varredura e de transmissão - Silva, Maria Rosa Bet de Moraes [UNESP]; Gregório, Elisa Aparecida [UNESP] (My University, 2006)
Purpose: To evaluate and correlate in the rabbit the possible changes caused by mitomycin C under the scleral flap in the ciliary epithelium with transmission electron microscopy (TEM) and scanning electron microscopy (SEM). Methods: The eyes of 32 albino rabbits were studied and divided in 4 experimental groups. The right eye (RE) was intended for the experimental groups and the left eye (LE) for the controls. Group I (G1) was formed by 8 eyes that received 0,5 mg/ml of mitomycin C under the scleral flap and were examined after 15 days. Group II (G2) differed from G1 only in the time of the exam, after 30 days. Group III (G3) was formed by 8 eyes that received 0,2 mg/ml of mitomycin C under the scleral flap and were examined after 15 days. Group IV (G4) differed from group 3 just in the time of the exam, after 30 days. In each eye the internal ciliary epithelium were examined with TEM. Results: The following changes in the internal ciliary epithelium were observed in groups G2, G3, and G4 with TEM: discontinuous and irregular basement membrane, more irregular and electron-dense nucleous, enlargement among interdigitation, edematous mitochondria and myelin figures. These alterations were not found in all the animals of the groups. Group G 1 did not present alterations. Roughness in groups G 1, G2, G3 and G4 were observed with SEM. In groups G 1 and G2 continuity solutions were also observed. Conclusion: Mitomycin C in 0,2 mg/ml and 0,5 mg/ml concentrations caused changes in the internal ciliary epithelium 15 and 30 days after, with TEM and SEM. There was no correlation between dosage, time and with TEM and SEM.
Effect of mitomycin c on the ciliary epithelium experimental study in rabbits with transmission and scanning electron microscopy
Keywords: Ciliary body (ciliary epithelium)/drug effects; Microscopy, electron; Microscopy, electron, scanning; Mitomycin; Rabbits